Penelopa, Demeter, Nike? - kobiece archetypy w czasach zagrożenia bezpieczeństwa z perspektywy genderowej analizy tekstów historycznych = Penelope, Demeter, Nike... - feminine archetypes in the times of unrest from the perspective of gender analysis of historical texts - Trzop, Beata; Szaban, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The issues discussed in the article relate to sociology of gender and gender discourse in the area of gender studies. The following research questions were asked in this paper: Is it possible to adapt gender discourse analysis to the context of national security threats and fights? - or in other words - To what extend the process of militarization constructs the roles of women? Thus, is it true that a soldier does not have gender? The authors attempt to rewrite the history of militant women.
Keywords: gender studies; rola kobiety; Powstanie Warszawskie - 1944; analiza pól semantycznych; the role of women; Warsaw Uprising; semantic field analysis